What Kind of Intervention Is Effective for Improving Subjective Well-Being Among Workers? A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Sakuraya, Asuka; Imamura, Kotaro; Watanabe, Kazuhiro; Asai, Yumi; Ando, Emiko; Eguchi, Hisashi; Nishida, Norimitsu; Kobayashi, Yuka; Arima, Hideaki; Iwanaga, Mai; Otsuka, Yasumasa; Sasaki, Natsu; et al. (Frontiers in Psychology, 2020)
Objectives: This study aimed to conduct a systematic review and meta-analysis of randomized controlled trials (RCTs) to improve subjective well-being (SWB), including evaluative, hedonic, and eudemonic well-being, and the mental component of quality of life (QOL) of working population. Methods: A literature search was conducted, using PubMed, Embase, PsycINFO, and PsycARTICLES. Eligible studies included those that were RCTs of any intervention, conducted among healthy workers, measured SWB as a primary outcome, and original articles in English. Study characteristics, intervention, outcomes, and results on SWB outcomes were extracted by the investigators independently. After a brief narrative summarizing and classifying the contents of the interventions, the included outcomes were categorized into each aspect of SWB (evaluative, hedonic, and eudemonic well-being and the mental component of QOL). Finally, the characteristics of the effective interventions for increasing each aspect were summarized and the pooled effect of interventions on SWB was investigated by a meta-analysis. Results: From the 5,450 articles found, 39 met the inclusion criteria for the systematic review. The interventions included in this review were classified into six categories (physical activity, ergonomics, psychological, environmental, multi-component intervention, and others). The meta-analysis from 31 studies showed the pooled effect of included interventions on SWB was significantly positive (standardized mean difference (SMD) = 0.52; 95% CI, 0.38–0.67). Subgroup analyses for separate types of interventions showed the effects of physical activity and psychological interventions (e.g., mindfulness, cognitive behavioral based approach, and other psychological interventions) were also significantly positive. Conclusion: The current study revealed the effectiveness of interventions for increasing SWB. Specifically, physical activity and psychological interventions (e.g., mindfulness, cognitive behavioral based approach, and other psychological interventions) may be useful for improving SWB.